CSF1R regulates monocyte subset differentiation and intracellular metabolism - Gallerand, Alexandre; Merlin, Johanna; Caillot, Zakariya; Delaby, Chloé; Bord, Elisa; Han, Jichang; Dolfi, Bastien; Castiglione, Alexia; Grenet, Sacha; Franceschini, Maxime; Jarretou, Gisèle; Zair, Fairouz N; et al. (Nature communications, 2025)
Monocytes are key circulating effectors of vascular homeostasis, innate immunity and inflammation. Following their generation in mouse bone marrow, classical (Ly6C ) monocytes are mobilized into the blood circulation where they mature into non-classical (Ly6C ) patrolling monocytes or are recruited into peripheral tissues where they differentiate into tissue resident or inflammatory macrophages. Monocytes and macrophages express CSF1R (CD115), the receptor for lineage-specific growth factors CSF1 and IL34. Here, we report that acute CSF1R blockade or genetic deletion negatively interferes with monocyte intracellular metabolism and reduces blood Ly6C monocytes in part by blunting differentiation of Ly6C monocytes. Based upon lineage-specific deletion of GFPT1 (Glutamine-Fructose-6-Phosphate Transaminase 1), the hexosamine biosynthetic pathway (HBP) is identified as a novel regulator of CSF1R expression and monocyte subset diversity. Our findings provide new insights into the link between CSF1R signaling, metabolic regulation, and monocyte survival and differentiation.